Feasibility of thiotepa addition to the fludarabine-busulfan conditioning with tacrolimus/sirolimus as graft vs host disease prophylaxis. Issue 8 (2nd July 2020) - Fox, María Laura; García-Cadenas, Irene; Pérez, Ariadna Martínez; Villacampa, Guillermo; Piñana, José Luis; Ortí, Guillermo; Montoro, Juan; Roldán, Elisa; Bosch Vilaseca, Anna; Martino, Rodrigo; Salamero, Olga; Saavedra, Silvana; et al.
Abstract: In classical reduced-intensity conditioning (RIC) regimens, including the fludarabine and busulphan (BF) combination, sirolimus and tacrolimus (SIR-TAC) as graft vs host disease (GVHD) prophylaxis has shown acceptable results. The outcomes of SIR-TAC in a more intense RIC regimen as Thiotepa-fludarabine-busulfan (TBF) have been hardly investigated. This retrospective study included all consecutive patients receiving an allogeneic hematopoietic stem cell transplantation for myeloid malignancies (January 2009–2017) conditioned with either TBF or BF and receiving SIR-TAC. Patients receiving TBF presented higher non-relapse mortality (31.6 vs 12.3%, p  = .01), along with shorter overall survival (51.8% vs 77.8%, p  < .01) at 2 years than patients treated with BF. There were no significant differences in the cumulative incidence of grade II–IV acute GVHD or moderate-severe chronic GVHD or relapse between both groups. These results suggest that TBF does not seem to improve the traditional RIC BF regimen, at least when associated with SIR-TAC prophylaxis.